A review on shell materials based on synthetic polymers for Micro-Encapsulated phase change materials(MEPCMs) - Abubakar, Abdullahi Musa; Yan, Kezhen; Huang, Junxian; Demirelli, Kadir (Springer, 2025)
Synthetic polymers are indispensable as shell materials in microencapsulated phase change materials (MEPCMs), providing essential protection to the PCM core and ensuring thermal and chemical stability. This review highlights that polymers such as melamine-formaldehyde, polyurethane, and polymethyl methacrylate (PMMA) are particularly advantageous due to their superior mechanical flexibility, high encapsulation efficiency, and broad compatibility with diverse PCMs. Advanced encapsulation techniques, like in-situ and interfacial polymerization, enable precise control over shell morphology and characteristics, facilitating the development of MEPCMs with tailored properties for applications in temperature-regulating building materials, durable asphalt pavements, thermal protection for electronics, and renewable energy storage. A critical analysis of recent studies reveals significant progress in enhancing the thermal reliability and energy storage capacity of these polymer-shell MEPCMs. However, key research gaps persist, particularly in reconciling the often competing demands of high thermal conductivity and robust mechanical strength, preventing PCM leakage over repeated thermal cycles, and mitigating the environmental concerns associated with certain polymer precursors. Future research avenues should prioritize the development of nano-enhanced polymer composites to improve thermal performance, alongside the pursuit of more sustainable and environmentally friendly encapsulation strategies. Addressing these challenges is crucial for unlocking the full potential of MEPCMs in next-generation thermal energy management systems.
Keywords: Synthetic polymers; Microencapsulated Phase Change Materials (MEPCMs); Shell materials; Thermal energy storage; Encapsulation techniques; Thermal properties